Study of genetic diversity potato samples microsatellite markers (Experimental biology, 2015)
We used the following methods: isolation and purification of DNA from potato, quantification and purity of the isolated DNA, DNA amplification primers, SSR- polyacrylamide gel electrophoresis, the construction of a dendrogram using UPGMA algorithm and a computer program TREECON. The studies used 7 pairs of microsatellite primers to assess polymorphism 48 grades of Kazakhstani and foreign selection, which together generate 41 amplification fragments ranging in size from 111 to 244 bp. Polymorphism loci studied was quite high and amounted to 97.6% . On the basis of SSR- alleles method of cluster analysis were identified genetic distances between 48 genotype of potatoes and tree was constructed.
Keywords: potato variet; DNA; SSR- marker locus; allele